Developing the Potential for Historical Educational Tourism Through Community Literacy Programs - Wahdah, Nur; Parinduri, Armayanti Akhiriyah; Lestari, Novilia; Dida, Zinedin (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2024)
The Jam Gadang area in Bukittinggi City has great potential to be developed as an educational tourism. Its potential includes history and culture, architecture and design, history education, and tourism. This research aims to find out how to develop the potential for educational tourism in the history of Jam Gadang through literacy programs, including what the potential for educational tourism in Jam Gadang, what are the principles for implementing literacy programs based on the culture and history of Jam Gadang and how this literacy program plays a role in the life and educational tourism activities in the history of Jam Gadang Bukittinggi. The method used in this research is qualitative research with a case study approach. Data sources were taken through interviews with several informants. The results of this research indicate that the public already knows that the Bukittinggi Jam Gadang has the potential to become a historical educational tourist attraction. Still, in reality, its implementation has not been optimal.